ANALISIS VEGETASI HUTAN LINDUNG GUNUNG TUMPA - Kainde, Reynold P.; Ratag, Semuel P.; Tasirin, Johny S.; Faryanti, D. (EUGENIA, 2011)
ABSTRACT   This research was carried out in the Mount of Tumpa Protection Forest from February to March 2003, aiming to asses Important Value (IV) Index.  Simple random sampling with plot was used to collect species data. The observation for collecting specie data was  number individual of each species, trees, poles diameter and species presence.  The data were analysed for density, relatif density, frequency, relatif frequency, dominancy, relatif dominancy and Important Values (IV) The results showed that at seedling level, Important Value of Tepu was the highest  (41,83%) and lowest was Calophyllum soulattri (10,03 %).  The highest Important Value at  the sapling level was Calamus sp (38,73%) and the lowest was Knema latericia (10,11%). The highest  Important Value at the pole level was Spathodea campanulata (74,01%) and the lowest was Dracontomelum mangiverum (10,05%).  The highest Important Value at tree level was Spathodea campanulata (88,86%) and the lowest was Calophyllum soulattri (10,22%). Keywords : Important Value Index, Vegetation Analysis